ORGANIZING STUDENTS' INDEPENDENT WORK AS A FACTOR OF FORMING PROFESSIONAL COMPETENCES - Karimova Dilfuza Abduraxmat qizi (Zeta Repository, 2023)
This article discusses the role of students' independent work in the formation of professional competencies in the training of personnel and its organization.